Phytochemical Investigation Of Extract/ Solvent Fractions Of Piper Nigrum Linn. Seeds And Piper Betle Linn. Leaves - SHILIKA SHETTY; K. K. VIJAYALAXMI (International Journal of Pharma and Bio Sciences, 2012)
Phytochemical analysis of extract/solvent fractions of two medicinal plants; Piper nigrum Linn. (seeds) and Piper betle Linn. (leaves) was conducted to detect the presence of various phytochemical constituents. These two plants are extensively used in Ayurvedic system of medicine. Each analysis was carried out in triplicate. The qualitative analysis of crude extract and solvent fractions of Piper nigrum Linn. and Piper betle Linn. revealed the presence of various phytochemicals of pharmacological significance such as, alkaloids, steroids, tannins, phenols, flavones etc.